Hispanic sources of the Society of Jesus in Japan: their research horizons (Tzintzun, Revista de Estudios Históricos, 2021)
This work presents the state of the matter of the two most researched Jesuitical sources during Japanâ€™s early modern evangelization period (15491639): the letters of Francisco Xavier and el Sumario de las cosas de Japón (Summary of the Things of Japan), written by the Jesuit Visitor to the East Indies, Alessandro Valignano. A general panorama of the research in the European, American and Japanese academic field is first presented. The multidisciplinary perspectives developed in the last decades from the historical, social, anthropological, religious, cultural, geographical and linguistic points of view will be shown afterwards.
Keywords: catholic missions in Japan; historiography; Francisco Xavier and Alessandro Valignano